From the Dialectological Archives: the Polish Dialect of Bražuolė (Trakai Area, 1992) - Коницкая, Елена Михайловна Михайловна (Slavistica Vilnensis, 2015)
The article provides dialectological recordings of Polish (the so-called polszczyznа kresowа) from the Trakai region, specifically Bražuolė and its surroundings, made during the expeditions in the 1990’s organized by the Department of Slavic Philology at Vilnius University. The Polish recordings are from an areal characterized sociolinguistically by the interface of four languages: the Polish dialect, Belarusian (po-prostu), Russian, and Lithuanian. These recordings reflect crucial and previously unidentified features of the sociolinguistic environment, as well as constitute historical evidence of language contact in Bražuolė and its surroundings. The data presented in the article can be used for further work on the history of language contacts in Lithuania.